PENGARUH KEPRIBADIAN TERHADAP KINERJA DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (STUDI PADA BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA KAB. PATI) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This research aims to determine the effect of personality on the performance with the job satisfaction and organizational commitment as mediation (A Studies on BPPKB in Pati ) . The research was conducted on employee in BPPKB PATI as many as 135 people. Statistical technique used is to test the validity of the components of the matrix, Cronbach alpha reliability test , multiple regression analysis, t test and test with adjusted r square . Results of the research known that personality has positive influence on job satisfaction. Personality is not a influence on organizational commitment. Job satisfaction has positive influence on organizational commitment. Personality has positive influence on performance. Job satisfaction has positive influence on performance. Organizational commitment has positive influence on performance. Job satisfaction does not mediate the effect of personality on performance. Organizational commitment did not mediate the effect of personality on performance. Job satisfaction and organizational commitment does not mediate the effect of personality on  performance. Keywords : Personality, Job satisfaction, Organizational Commitment and Performance